Isolation and Characterization of Novel Marine Bacterium from the Marine Soil Sample and its Antimicrobial Efficacy of the Secondary Metabolites: Pharmaceutical Science-Marine Biotechnology for better medical care - Subbiah Latha; Palanisamy Selvamani; Thangavelu Prabha (International Journal of Life Science and Pharma Research, 2022)
The marine bacterium was widely recognized as a natural manufacturer of novel bioactive secondary metabolites during the last decades, making the marine ecosystems a huge treasure of novel isolates. Marine coastal areas of the southern part of India have huge varieties of ecosystems that produce many marine microbes and organisms which are considered as a perennial source of many potential drug leads. This study focuses on the isolation of marine soil samples collected from the shores of the Bay of Bengal at Kanyakumari, Tuticorin, and Mandapam and followed by the characterization of the novel marine bacterium from that soil sample for the secondary metabolites production with potential pharmacological importance. The isolated pure culture from colonies was cultured and taxonomically characterized by gram staining and other supported biochemical tests. Further, from the genetic analysis results through 16s rDNA sequencing and by comparing the nucleotide homology and phylogenetic analysis of the organisms it was confirmed as “Paenibacillus dendritiformis and Paenibacillus thiaminolyticus”. Moreover, it was found that the bacterial isolates produced the inhibitory activity to other bacterial strains including both gram-positive and gram-negative bacteria at a concentration of 32 µl/ml. Thus, the bacterial isolates were found to produce secondary metabolites that comprise antimicrobial components and enzymes of commercial importance. Henceforth, this preliminary study looks promising and may lead to the discovery of potential antibiotics and other bioactive compounds.